2003
DOI: 10.1016/s0168-9002(03)00721-6
|View full text |Cite
|
Sign up to set email alerts
|

Technical design aspects of Feasibility Study-II

Abstract: Feasibility Study-II examined a high-performance Neutrino Factory providing 1 × 10 20 neutrinos per year aimed at a long-baseline detector. The Study was sponsored jointly by BNL and the Neutrino Factory and Muon Collider Collaboration (MC) and is based on a 1 MW proton driver operating at 24 GeV, i.e., an upgraded version of the AGS accelerator. Compared with the earlier FNAL-sponsored study (Feasibility Study-I), there is a sixfold improvement in performance. Here we describe details of the implementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Studies [30][31][32][33][34][35] so far have shown that the Neutrino Factory gives the best performance over virtually all of the parameter space; its time scale and cost remain, however, important question marks. Super-beams have many components in common with the Neutrino Factory.…”
Section: Precision Measurements and Sensitive Searchesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies [30][31][32][33][34][35] so far have shown that the Neutrino Factory gives the best performance over virtually all of the parameter space; its time scale and cost remain, however, important question marks. Super-beams have many components in common with the Neutrino Factory.…”
Section: Precision Measurements and Sensitive Searchesmentioning
confidence: 99%
“…This detector is assumed to have an appearance ν µ threshold rising linearly from 0 at 4 GeV to its final value at 20 GeV. Systematic uncertainties of 2.5% on the signal and 20% on the background 35 . For more details see [217,349].…”
Section: Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…The muon decays µ + → e + ν eνµ and µ − → e −ν e ν µ provide a very well known two-flavor neutrino flux [91] with energies in the range E ν ∈ [0, E µ ]. Neutrino Factory designs have been proposed in Europe [92,93], the US [94][95][96][97], and Japan [98]. The dedicated International Scoping Study for a future Neutrino Factory and Super-Beam facility [43] showed that, provided sufficient resources, an accelerator complex capable of providing about 10 21 muon decays of a given polarity per year can be built.…”
Section: Oscillation Probabilities At the Neutrino Factory In The (3+mentioning
confidence: 99%